The Influence of Audit Committee Quality and Internal Auditor Objectivity Toward The Prevention of Fraudulent Financial Reporting(A Survey in BUMN of Indonesia) - Angrita Denziana (International Conference On Law, Business and Governance (ICon-LBG), 2013)
It requires information quality, and free from distortion. Some cases both nationally and internationallyindicate the occurrence of irregularities in financial reporting due to the weakness ofthe company'sinternal control system, and the audit committeehas not functioned optimally, resulting in low quality offinancial reporting. The research study uses explanatory method. The data were collected through surveytechnique by distributing questionnaires to SOEs in Indonesia. The respondents involve audit committeeand internal auditors. Before the data were used to test the hypothesis, it should tested the validity andreliability of data. The data have been analyzed by using partial lisquare descriptive analysis modeling totest the hypotheses.The results concluded that, 1) the quality of the audit committee have affect on the prevention offraudulent financial reporting, 2) objectivity of internal auditor have affect on the prevention of fraudulentfinancial reporting.